Two-metal-edge extended X-ray absorption fine structure analysis of oxygen octahedral rotation in SrTiO3 using the reverse Monte Carlo method - Kai Kamijo; Nobuo Nakajima; Dongxiao Fan; Andris Anspoks (Journal of Synchrotron Radiation)
A three-dimensional analysis method for X-ray absorption spectra, combining two-metal-edge extended X-ray absorption fine structure (EXAFS) analysis with reverse Monte Carlo simulations, was applied to study the cubic-to-tetragonal phase transition in SrTiO3 as a dielectric standard. This method allows for the evaluation of both the static distribution and the dynamic motion of atoms, including oxygen. The optimized clusters reveal that the TiO6 octahedron can rotate up to 2.7° below the phase transition temperature, driven by reduced A-site Sr dynamics. Within the framework of conventional EXAFS analysis, the high-precision determination of atomic positions using the two-metal-edge analysis for ternary materials enhances the detection of light elements, and the method is applicable to bimetallic oxides and nitrides.